1998
DOI: 10.1073/pnas.95.13.7475
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic and oncogenic properties of the small G protein Rap1b

Abstract: It has been widely reported that the small GTP-binding protein Rap1 has an anti-Ras and antimitogenic activity. Thus, it is generally accepted that a normal physiological role of Rap1 proteins is to antagonize Ras mitogenic signals, presumably by forming nonproductive complexes with proteins that are typically effectors or modulators of Ras. Rap1 is activated by signals that raise intracellular levels of cAMP, a molecule that has long been known to exert both inhibitory and stimulatory effects on cell growth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
116
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 127 publications
(124 citation statements)
references
References 30 publications
6
116
2
Order By: Relevance
“…Other reports have suggested that Rap1a expression in Wistar Rat thyroid (WRT) cells promotes differentiation without affecting cell proliferation (42). Nevertheless, the present results are consis- tent with our previous observation using Swiss 3T3 cells (17) and extend the mitogenic effect of Rap1b to a differentiated system, the thyroid cell, where cAMP physiologically acts as a bona fide comitogen. In this model, Rap1b enhances the mitogenic response while maintaining differentiation.…”
Section: Rap1b Enhances the Mitogenic Response To Camp While Maintainingcontrasting
confidence: 54%
See 4 more Smart Citations
“…Other reports have suggested that Rap1a expression in Wistar Rat thyroid (WRT) cells promotes differentiation without affecting cell proliferation (42). Nevertheless, the present results are consis- tent with our previous observation using Swiss 3T3 cells (17) and extend the mitogenic effect of Rap1b to a differentiated system, the thyroid cell, where cAMP physiologically acts as a bona fide comitogen. In this model, Rap1b enhances the mitogenic response while maintaining differentiation.…”
Section: Rap1b Enhances the Mitogenic Response To Camp While Maintainingcontrasting
confidence: 54%
“…Exogenous expression of Rap1b in Swiss 3T3 fibroblasts was sufficient to endow these cells with both mitogenic and tumorigenic properties (17). In that report, we emphasized that the mitogenic effects of Rap1b were linked to its ability to promote S phase entry and introduced the hypothesis that Rap1b can be viewed as a conditional oncogene.…”
mentioning
confidence: 91%
See 3 more Smart Citations